2018
DOI: 10.12659/msm.910465
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Static and Dynamic Intensity-Modulated Radiotherapy Combined with Chemotherapy for Patients with Locally Advanced Nasopharyngeal Carcinoma Improves Survival and Reduces Brainstem Toxicity

Abstract: BackgroundIntensity-modulated radiotherapy (IMRT) is the standard treatment for patients with nasopharyngeal cancer (NPC). However, the dose-volume criteria for adjacent anatomically normal organs at risk (OARs) remain controversial. The aim of this study was to evaluate the effects of higher than conventional doses of static and dynamic IMRT on the locoregional control of NPC, patient survival, and brainstem radiation toxicity.Material/MethodsPatients (n=186) with stage III and stage IVa NPC underwent high-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Brainstem dose is almost always a concern in radiation planning, in our analysis, the brainstem was included but changes in FA values were not significant. Previous research showed brainstem toxicity was reduced in patients treated with static Intensity-modulated radiotherapy (IMRT) (0.07%) and dynamic IMRT (0.08%) [32]. We speculated that due to the application of IMRT, the brain stem has been rarely damaged by radiation, which is consistent with previous research.…”
Section: Discussionsupporting
confidence: 87%
“…Brainstem dose is almost always a concern in radiation planning, in our analysis, the brainstem was included but changes in FA values were not significant. Previous research showed brainstem toxicity was reduced in patients treated with static Intensity-modulated radiotherapy (IMRT) (0.07%) and dynamic IMRT (0.08%) [32]. We speculated that due to the application of IMRT, the brain stem has been rarely damaged by radiation, which is consistent with previous research.…”
Section: Discussionsupporting
confidence: 87%
“…NPC is a malignant disease of the head and neck area and causes 34.1 million deaths annually. [ 16 ] The disease is characterized by unique geographic, etiologic, and biologic features. As the widely application of intensity modulated radiotherapy and chemotherapy, the survival rate and quality of NPC patients have increased largely.…”
Section: Discussionmentioning
confidence: 99%
“…However, the causes of NPC and treatment strategies are different from those of other head and neck cancers ( 25 ). The prognosis of NPC patients has considerably improved with the combined use of magnetic resonance imaging, intensity-modulated radiotherapy (RT), and concurrent chemoradiation ( 26 , 27 ). NPC is highly sensitive to RT and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%